ATRIBUT DESTINASI YANG MEMPENGARUHI LOYALITAS WISATAWAN BERKUNJUNG KE KAWASAN SANUR - Nusantini, Ni Luh Ayu (Jurnal Master Pariwisata (JUMPA), 2016)
Sanur is one of the most attractive and renowned beach tourist destinations in Bali. However, there is no particular study so far to determine the influential attributes on Sanur, as well as the factors which affecting tourist’ opinion to visit this area. The purposes of this research are to determine the dominant attributes to determine visitors’ perception toward tourism attributes, to determine tourist loyalty on visiting Sanur area. This research was conducted by interviewing 100 domestic and foreign visitors who reside in the area at the time of research by accidental sampling method. Information regarding the trend of the visitors was gathered from ten respondents including business owners and local tourist authority by purposive sampling method. The research found that factors which dominantly influent tourist’ perception are ambience,beauty of scenery and accessibility. The ambience as the highest mean score, while the value of sport and outdoor activities is the lowest. The interest of both domestic and international tourist has been constantly high, where recommendation commitment is more preferable compared to other dimension (repurchasing and branding commitment).
Keywords: Perception; Tourism Attribute; Visiting Loyalty; Sanur Area.